2017
DOI: 10.21475/poj.10.04.17.pne707
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNA elements from genomic data of European hazelnut (Corylus avellana L.) and its close relatives

Abstract: Plant microRNAs (miRNAs) are small and non-coding endogenous RNAs which have numerous regulatory roles in cells. These critical players regulate pathways either by inducing translational repression or messenger RNA (mRNA) decay. Newly developed bioinformatics tools and computational methods have been increased to identify miRNAs with their targets inside the genome. In this study, we predicted and identified 57 putative miRNAs through Corylus avellana (C. avellana) genomic data in silico. We also predicted som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…All of these miRNAs could be assigned to 165 families. We identified 40, 37 and 38 members in the miR171, miR396 and miR482 families, respectively, suggesting that our results are consistent with the in silico miRNA prediction of the European hazel genome [23]. Clearly, the in silico Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…All of these miRNAs could be assigned to 165 families. We identified 40, 37 and 38 members in the miR171, miR396 and miR482 families, respectively, suggesting that our results are consistent with the in silico miRNA prediction of the European hazel genome [23]. Clearly, the in silico Fig.…”
Section: Discussionsupporting
confidence: 87%
“…By mining genomic data in silico, 57 putative miRNAs were predicted and identified in C. avellana 'Jefferson' (OSU 703.007) [22][23][24]. In the European hazel genome, miR171, miR396, miR482, and miR2118 families were found as in silico expressed putative miRNAs [23].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are ubiquitous post-transcriptional regulators in plants and a previous study identified putative miRNA genes in the draft C. avellana cv. Jefferson genome (Avsar and Aliabadi, 2017). In the Tombul genome, 153 putative conserved miRNA genes were annotated, including members of 52 different miRNA families (Table S11).…”
Section: Corylus Avellana Micrornas Are Regulators Of Development Andmentioning
confidence: 99%
“…In short-term solutions, agricultural residues produced on a provincial scale can play a significant role, as they entail fairly low costs and great accessibility. For instance, Turkey is one of the major hazelnut producers, and hazelnut is the most important tree nut crop for the country's economy; hence, the Turkish hazelnut cultivar's genome has recently been sequenced to unravel the critical properties for crop improvement (Avşar and Esmaeili Aliabadi 2017;Lucas et al 2021). Most hazelnut production in Turkey occurs in Ordu, Samsun, and Giresun near the Black Sea Coast.…”
Section: Pro-bio Scenariomentioning
confidence: 99%